PERAN GURU SEBAGAI MODEL DALAM PEMBELAJARAN KARAKTER DAN KEBAJIKAN MORAL MELALUI PENDIDIKAN JASMANI - Dimyati Dimyati (Jurnal Cakrawala Pendidikan, 2010)
Abstract: The Teachers Role as a Model in Teaching Character and MoralVirtues through Physical Education. Problems of students bad character andmorality always appear in the field of education. This may result from the fact thateducation in Indonesia emphasizes intellectual development only, while otheraspects, such as personality, affective factors, and moral virtues, receive lessattention. Schools and teachers actually play an important role and have aresponsibility for students' learning both in the cognitive and affective aspects. Inother words, improvement of and emphasis on the cognitive aspect such as skills inreading, language, mathematics, and science aimed at preparing students to enterthe global world should be balanced against the improvement of their affectiveaspect. This means that character building and moral virtue teaching must not beignored.Keywords: teacher as model, teaching character